2020
DOI: 10.3390/ph13120459
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Cannabidiol Metabolites in Serum and Urine from Healthy Individuals Treated with Pharmaceutical Preparations of Medical Cannabis

Abstract: The use of cannabis flowering tops with standardized amounts of active phytocannabinoids was recently authorized in several countries to treat several painful pathological conditions. The acute pharmacological effects and disposition of Δ-9-tetrahydrocannabinol (THC), cannabidiol (CBD), their acidic precursors and THC metabolites after oil and decoction administration have been already described. In this study, the disposition of CBD metabolites: 7-carboxy-cannabidiol (7-COOH-CBD), 7-hydroxycannabidiol (7-OH-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…This experiment with vaporized medical cannabis has been the third part of a study on the disposition of THC, CBD, their acidic precursors, and their metabolites following the administration of the three most common formulations of medical cannabis: Decoction, oil, and vaporized flowering tops [7,8]. In this regard, it is worth noticing that:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This experiment with vaporized medical cannabis has been the third part of a study on the disposition of THC, CBD, their acidic precursors, and their metabolites following the administration of the three most common formulations of medical cannabis: Decoction, oil, and vaporized flowering tops [7,8]. In this regard, it is worth noticing that:…”
Section: Discussionmentioning
confidence: 99%
“…We recently investigated the disposition of THC, CBD, their precursors, and their principal metabolites in biological matrices of healthy individuals treated with oral decoction and oil, the most used medical cannabis herbal preparations [7,8]. We found that the aqueous preparation was generally better absorbed than the oil, even if it contained a minor amount of THC, THCA-A, and CBD.…”
Section: Introductionmentioning
confidence: 99%
“…9,11 The most common metabolites of CBD are 7-COOH-CBD, the inactive metabolite, 7-OH-CBD, the active metabolite, and the 6-α-OH-CBD and 6-β-OH-CBD minor metabolites. 12 However, CBD metabolism is complex, and over 40 phase I metabolites alone have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CBD has the potential to inhibit CYP1A2, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, UGT1A9, and UGT2B7 9,11 . The most common metabolites of CBD are 7‐COOH‐CBD, the inactive metabolite, 7‐OH‐CBD, the active metabolite, and the 6‐α‐OH‐CBD and 6‐β‐OH‐CBD minor metabolites 12 . However, CBD metabolism is complex, and over 40 phase I metabolites alone have been identified.…”
mentioning
confidence: 99%
“…Previous studies have determined the levels of CBD or its metabolites in biological samples after medical cannabis consumption [ 17 , 18 , 19 , 20 , 21 , 22 ]. Although these studies were valuable, no analytical assay exists for the simultaneous determination of CBD and its main metabolites, 7-hydroxycannabidiol (7-OH-CBD), 6-α-hydroxycannabidiol (6-α–OH–CBD) and 6-β-hydroxycannabidiol (6-β–OH–CBD) in serum samples of individuals treated with CBD-based pharmaceuticals or medical cannabis.…”
Section: Introductionmentioning
confidence: 99%